Iron-based catalyst (Fe2-xNixTiO5) for tar decomposition in biomass gasification. (15th September 2021) - Ruivo, L.C.M.; Pio, D.T.; Yaremchenko, A.A.; Tarelho, L.A.C.; Frade, J.R.; Kantarelis, E.; Engvall, K.
Highlights: A facile method is proposed to process Fe2-x Nix TiO5 catalysts. Formation of Fe-Ni alloy by pre-activation is effective to improve performance. 10%Ni-FT exhibited the highest activity for tar decomposition (78%). Controlled redox conditions is a key parameter in maximizing catalytic activity. Abstract: In this study, a novel Fe2-x Nix TiO5 catalyst for potential applications in biomass gasification gas cleaning/upgrading was investigated. The material was successfully synthesized through combined mechanical activation and microwave firing. Catalytic steam reforming was studied in a fixed bed tubular reactor, using a mixture of toluene and naphthalene as model tar compounds as well as downstream a fluidized bed gasifier. Fe2-x Nix TiO5 catalyst showed high activity in converting the model compounds at temperatures higher than 700 °C. The catalyst exhibited a tar conversion of 78% at 800 °C when exposed to biomass-derived gas from a bubbling fluidized bed gasifier. Nevertheless, the catalytic activity declined with increased time on stream due to structural changes in iron active phases, caused by redox conditions of the producer gas. Furthermore, thermodynamic calculations suggest that sulfur chemisorption on the nickel surface, may also contribute to the catalyst deactivation.